HUBUNGAN PEMBERIAN MAGNESIUM SULFAT (MgS04) PADA PERSALINAN PRE-EKLAMPSIA/EKLAMPSIA TERADAP KEJADIAN ASFIKSIA DI RUMAH SAKIT BHAYANGKARA MAKASAR - Mardiana Stefania Bhoko (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2020)
MPS's mission is to reduce maternal and neonatal morbidity and mortality through strengthening the health system to ensure access to interventions that are cost effective based on scientific evidence of quality, empower women, families and communities through activities that promote maternal and newborn health, and ensure that health maternal and neonatal is promoted and preserved as a priority for national development programs. In Indonesia the incidence of preeclampsia and eclampsia ranges from 3 - 10%. According to world data, WHO estimates that more than 160,000 women die each year due to preeclampsia and eclampsia, and this is a cause of death that has been going on for decades. There is still no agreement regarding the exact cause of seizures in patients with eclampsia. Magnesium Sulphate (MgSO4) is one of the selected drugs to prevent seizures in preeclampsia and eclampsia, where the use of magnesium sulfate is effective and safe. The aim of this study was to determine the association of Magnesium Sulphate (MgSO4) in the delivery of Preeclampsia / Eclampsia to Asphyxia in Newborns in 2013 Makasar Bhayangkara. In this study the variables studied were Magnesium Sulphate, Asphyxia. The type of research used in this study is the type of "Case Control" research which is an analytical survey study that deals with how risk factors are studied using a "retrospective" approach. The sample in this study were all patients who fulfilled the inclusion and exclusion criteria who were admitted to Makasar's Bhayangkara Hospital in the January-December 2013 period. For the control group, the sample was taken using proposive sampling. In this study, it can be seen from the chi-square results that there is no correlation between the incidence of asphyxia and the administration of MgSO4 supported by chi-square results, p = 0.65 where p <0.05 Ho is rejected but in this study p> 0.05 or 0.65 > 0.05 means that Ho is accepted. Keywords: MGS04, Asphyxia